Singapore’s ’30 by 30’ Strategy : Can Food Self-Production Be Achieved? - Teng, Paul (2019)
The recent announcements in Parliament to raise Singapore’s food self-production level from the current 10% to 30% of total food needs by 2030, the “30 by 30” strategy, have raised some pertinent questions on capacity, investment and exportability.